2016
DOI: 10.1093/jac/dkw336
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NS5A polymorphisms and their impact on response rates in patients with HCV genotype 2 treated with daclatasvir-based regimens

Abstract: High SVR rates were achieved in patients infected with GT2 treated with daclatasvir-based regimens irrespective of GT2 subtype or baseline NS5A polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…However, the NS5A F28C polymorphism was only detected in patients infected with subtype 2c, and 11 of 18 GT2c‐infected patients carried this polymorphism at baseline. Similarly, in studies with daclatasvir the NS5A polymorphism F28C was predominantly observed in patients infected with subtype 2c . Although the presence of NS5A F28C in a GT2a replicon was found to reduce the in vitro activity of daclatasvir and ledipasvir, baseline presence of this polymorphism in GT2c‐infected patients did not appear to affect the outcome to the daclatasvir‐based regimens studied .…”
Section: Discussionmentioning
confidence: 86%
“…However, the NS5A F28C polymorphism was only detected in patients infected with subtype 2c, and 11 of 18 GT2c‐infected patients carried this polymorphism at baseline. Similarly, in studies with daclatasvir the NS5A polymorphism F28C was predominantly observed in patients infected with subtype 2c . Although the presence of NS5A F28C in a GT2a replicon was found to reduce the in vitro activity of daclatasvir and ledipasvir, baseline presence of this polymorphism in GT2c‐infected patients did not appear to affect the outcome to the daclatasvir‐based regimens studied .…”
Section: Discussionmentioning
confidence: 86%
“…Some of these samples had amino acid polymorphisms within the NS5A N-terminal region at positions associated with resistance to some NS5A inhibitors (10, 13, 14). For example, methionine (M) and leucine (L) are commonly seen at NS5A amino acid position 31 of genotype 2; genotype 2a and 2b samples with NS5A M31 are less susceptible to daclatasvir, ledipasvir, and elbasvir than those with L31 (23, 26). In the panel of patient samples that we analyzed, 5/6 of the genotype 2a and 4/11 of the genotype 2b samples had M31 in NS5A.…”
Section: Resultsmentioning
confidence: 99%
“…Ledipasvir has EC 50 s of 4 to 31 pM for genotype 1 but has reduced potency against other genotypes, especially for genotypes 2a and 3a (EC 50 s, ≥16,000 pM) (20). Genotype 2 with the common NS5A M31 polymorphism is less susceptible to daclatasvir than genotype 2 with NS5A L31 (genotype 2a with M31, EC 50 of 6,700 pM; genotype 2b with M31, EC 50 of 64,000 pM) (26). Genotype 2b with the NS5A M31 polymorphism is also less susceptible to elbasvir (EC 50 , 3,000 pM) than genotype 2b with L31 (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Gt 2a, HCV-NS5A F28S, L31M, C92R, and Y93H are the major resistance mutations described 42. Zhou et al 43. evaluated NS5A polymorphisms and their impact on response rates in patients with Gt 2 infection who were treated with DCV-based regimens.…”
Section: Onset Of Resistance: a Real Clinical Problem?mentioning
confidence: 99%